A review on the role of MEG8 lncRNA in human disorders - Soudeh Ghafouri-Fard; Tayyebeh Khoshbakht; Bashdar Mahmud Hussen; Mohammad Taheri; Seyedpouzhia Shojaei (Cancer Cell International, 2022)
Abstract Maternally expressed 8 (MEG8) is a long non-coding RNA which is expressed in the nucleus. It is highly expressed in adrenal, placenta and brain. Recent studies have shown contribution of MEG8 in different disorders ranging from neoplastic ones to diabetic nephropathy, atherosclerosis, ischemic stroke, trophoblast dysfunction and abortion, Henoch-Schonlein purpura and osteoarthritis. It has an oncogenic role in the development of lung, pancreatic and liver cancer. In the current review, we summarize the role of this lncRNA in mentioned disorders, based on the evidence obtained from in vitro, in vivo and human studies.